2005
DOI: 10.1108/09513570510600765
|View full text |Cite
|
Sign up to set email alerts
|

Knowing “the price of everything and the value of nothing”: accounting for heritage assets

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 29 publications
2
47
0
3
Order By: Relevance
“…This is sometimes presented as a confl ict between traditional views of worthiness in a continued process of conservation of authentic materials for the purpose of refl ective sociocultural learning -herein considered as a cultural 'bathing' effect for visitors out of their everyday experience -as opposed to modernist views that museums should alter their approach to be more entertaining and accessible (often through the adoption of new technology), deemed to be relevant to integration within current everyday lifestyles and behaviours. Although there have been evident attempts to reach a balanced view by some of the debate participants (Gilmore and Rentschler, 2002), the two sides can often be perceived as taking mutually exclusive positions in purpose, design, funding, activity and desired outcomes between, on the one side, a strong priority given to culture and custodianship concerns within a largely humanistic, learning orientation (Hewison, 1987;Fowler, 1992;Goulding, 1999Goulding, , 2000aGoulding, , 2000bHooper et al, 2005) and, on the other, to predominantly commercial and managerialist concerns within a technologically up to date, marketing orientation (Cossons, 1985;Hall, 1997;Lennon and Graham, 2001;Carmen and José, 2008).…”
Section: Background and Literaturementioning
confidence: 99%
“…This is sometimes presented as a confl ict between traditional views of worthiness in a continued process of conservation of authentic materials for the purpose of refl ective sociocultural learning -herein considered as a cultural 'bathing' effect for visitors out of their everyday experience -as opposed to modernist views that museums should alter their approach to be more entertaining and accessible (often through the adoption of new technology), deemed to be relevant to integration within current everyday lifestyles and behaviours. Although there have been evident attempts to reach a balanced view by some of the debate participants (Gilmore and Rentschler, 2002), the two sides can often be perceived as taking mutually exclusive positions in purpose, design, funding, activity and desired outcomes between, on the one side, a strong priority given to culture and custodianship concerns within a largely humanistic, learning orientation (Hewison, 1987;Fowler, 1992;Goulding, 1999Goulding, , 2000aGoulding, , 2000bHooper et al, 2005) and, on the other, to predominantly commercial and managerialist concerns within a technologically up to date, marketing orientation (Cossons, 1985;Hall, 1997;Lennon and Graham, 2001;Carmen and José, 2008).…”
Section: Background and Literaturementioning
confidence: 99%
“…Prior to the 1980s most public NFP entities were subject to only limited reporting obligations regarding their functions of stewardship of HCA (Easton, 1997;Lehman, 2001;Hooper & Kearins, 2005). Commonly, they were required to account for funds employed in the acquisition, maintenance, extension, replacement, and disposal of such assets, and to report on their 'operations' for specified stakeholders (usually limited to government ministries), using a range of means for 'valuing' the HCA held under their stewardship.…”
Section: Introductionmentioning
confidence: 99%
“…There exists considerable scepticism about measuring heritage assets for inclusion on financial statements. Hooper, Kearins and Green (2005) in a study of museums in New Zealand found that museum managers sought to reflect curatorship values in their annual reports and rejected the application of accounting standards requiring the inclusion of heritage assets.…”
Section: The Measurement Of Heritage Assetsmentioning
confidence: 99%